Effects of tea and coffee on cardiovascular disease risk - Bønn, S.; Ward, Natalie; Hodgson, J.; Croft, K. (2012)
Tea and coffee have been associated with risk of cardiovascular disease (CVD), both positively and negatively. Epidemiological data suggest that black and green tea may reduce the risk of both coronary heart disease and stroke by between 10 and 20%. Experimental and clinical trial data generally indicate either neutral or beneficial effects on risk factors and pathways linked to the development of CVD. Controversy still exists regarding the effects of coffee, where there have been concerns regarding associations with hypercholesterolaemia, hypertension and myocardial infarction. However, long term moderate intake of coffee is not associated with detrimental effects in healthy individuals and may even protect against the risk of developing type 2 diabetes. The detrimental effects of coffee may be associated with the acute pressor effects, most likely due to caffeine at high daily intakes, and lipids from boiled coffee can contribute to raised serum cholesterol.Genetic polymorphisms in enzymes involved in uptake, metabolism and excretion of tea and coffee compounds are also associated with differential biological effects. Potential mechanisms by which tea and coffee phytochemicals can exert effects for CVD protection include the regulation of vascular tone through effects on endothelial function, improved glucose metabolism, increased reverse cholesterol transport and inhibition of foam cell formation, inhibition of oxidative stress, immunomodulation and effects on platelet function (adhesion and activation, aggregation and clotting). The phytochemical compounds in tea and coffee and their metabolites are suggested to influence protective endogenous pathways by modulation of gene-expression. It is not known exactly which compounds are responsible for the suggestive protective effects of tea and coffee. Although many biologically active compounds have been identified with known biological effects, tea and coffee contain many unidentified compounds with potential bioactivity.